Angiographic findings in cases with a history of severe retinopathy of prematurity treated with anti-VEGFs: Follow-up to age 6 years - ÇELİKER ATABERK, HANDE; ŞAHİN, ÖZLEM (SPRINGER, 2021)
Purpose To report the effects of anti-vascular endothelial growth factor (VEGF) treatment in vascular development for cases of acute retinopathy of prematurity (ROP) using fluorescent angiography (FA) and to present the results of our observational approach to retinal sequelae. Methods A total of 31 eyes in 19 patients with a history of treatment with anti-VEGF agents for classic type 1 ROP and aggressive posterior ROP who underwent FA between March 2014 to February 2020 were reviewed. Angiograms of retinal developmental features of patients aged 4 months to 6 years were examined. Results The patients mean gestational age were 26.06 +/- 1.90 weeks and the mean birth weight were 837.68 +/- 236.79 g. All cases showed various abnormalities at the vascular and avascular retina, and the posterior pole. All but one case showed a peripheral avascular area on FA evaluation during the follow-up period. We did not apply prophylactic laser treatment to these avascular retina. On the final examination, except one case, we did not observe any late reactivation in any patients. Conclusion FA is an important tool for assessing vascular maturation in infants. Every leakage should not be assumed to be evidence of late activation, as some leaks may be related to vascular immaturity. Retinal vascularization may not be completed in all patients, however this does not mean that all these patients need prophylactic laser application. Our observational approach may be more daring than the reports frequently encountered in the literature, but it should be noted that unnecessary laser treatment will also eliminate all the advantages of anti-VEGF treatment.
Keywords: Anti-VEGFs; Fluorescein angiography; Late recurrence; RetCam; Retinopathy of prematurity; AGGRESSIVE POSTERIOR RETINOPATHY; RETINAL VASCULAR DEVELOPMENT; PERSISTENT AVASCULAR RETINA; INTRAVITREAL BEVACIZUMAB; FLUORESCEIN ANGIOGRAPHY; TYPE-1 RETINOPATHY; INTERNATIONAL CLASSIFICATION; LATE REACTIVATION; TREATMENT FAILURE; ZONE I